Dipole excitations of Ar substrate in contact with Na clusters - Dinh, P. M.; Reinhard, Paul-Gerhard; Suraud, E. (Surface Science, 2009)
We analyze the excitation of Ar substrate in contact with Na clusters using a previously developed hierarchical model for the description of the system constituted of a highly reactive metal cluster in contact with a rather inert substrate. Particular attention is paid to the dipole excitation of the Ar atoms and the energy stored therein. The Na clusters are considered at different charge states, anions, cations, and neutral clusters for the case of deposition and a highly ionized cluster embedded in a matrix. It is found that the dipole polarization of the Ar atoms stores the largest fraction of energy in the case of charged clusters. Some, although smaller, polarization is also observed for polar clusters, as Na6. The effect is predominantly induced by the electrostatic interaction. © 2008 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-07-24
Keywords: Deposition dynamics; Dipole excitation; Hierarchical approach; Rare gas surface; TDDFT